Quantitative genetics of lodgepole pine (Pinus contorta) wood quality traits in Sweden - Hayatgheibi, Haleh (2018)
Stem bending, breakage, and general instability of lodgepole pine has been a major problem in northern Sweden due to low stem stiffness. The overall aim of this thesis was to evaluate the potential incorporation of wood quality traits into lodgepole pine advanced breeding programs. To achieve this, 823 increment cores were sampled from 207 half-sib families at two progeny trials of lodgepole pine and genetic variations in wood density, microfibril angle (MFA), modulus of elasticity (clearwood stiffness; MOEs), radial fibre width (RFW), tangential fibre width (TFW), fibre wall thickness (FWT), and fibre coarseness (FC) were characterised. To quantify genotype by environment interactions (G × E) for growth and stiffness and to evaluate performance of provenances, diameter at breast height (DBH) and dynamic stiffness of standing trees (MOEtof) were studied, using six 33-36 year-old lodgepole progeny trials within three different breeding zones in northern Sweden. To evaluate genetic gains in selection for an early MFA transition from juvenile to mature wood, six different regression functions were fitted to the MFA profile of each tree to delineate the age variation in MFA transition. Narrow-sense heritability estimates (ℎ2) ranged from 0.10 to 0.32 for DBH and from 0.18 to 0.76 for wood quality traits. Unfavourable genetic correlations between growth and stiffness were observed, implying that selection for a 1% increase in DBH alone, would confer 5.5% and 2.3% decreases in lodgepole pine MOEs and MOEtof, respectively. Results of the studies in this thesis indicate that simultaneous improvement of DBH and stiffness is achievable when an optimal selection index combining both traits is implemented. Additionally, it is possible to select for an earlier MFA transition from juvenile to mature wood, and thus, decreasing the proportion of the log containing juvenile wood in lodgepole pine selective breeding programs. Finally, G × E was only significant for stiffness within the northern most breeding zone. To achieve the ...